2014
DOI: 10.1093/mnras/stu1286
|View full text |Cite
|
Sign up to set email alerts
|

Physical properties, star-spot activity, orbital obliquity and transmission spectrum of the Qatar-2 planetary system from multicolour photometry★

Abstract: We present seventeen high-precision light curves of five transits of the planet Qatar-2 b, obtained from four defocussed 2m-class telescopes. Three of the transits were observed simultaneously in the SDSS g ′ r ′ i ′ z ′ passbands using the seven-beam GROND imager on the MPG/ESO 2.2-m telescope. A fourth was observed simultaneously in Gunn grz using the CAHA 2.2-m telescope with BUSCA, and in r using the Cassini 1.52-m telescope. Every light curve shows small anomalies due to the passage of the planetary shado… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
52
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 60 publications
5
52
0
Order By: Relevance
“…According to Eq. (1) of Mancini et al (2014), the same starspot can be observed after consecutive transits or after some orbital cycles, presuming that in the latter case, the star performs one or more rotations around its axis. Since the projected obliquity measured by the RM effect (see Sect.…”
Section: Hat-p-36 Starspotsmentioning
confidence: 74%
“…According to Eq. (1) of Mancini et al (2014), the same starspot can be observed after consecutive transits or after some orbital cycles, presuming that in the latter case, the star performs one or more rotations around its axis. Since the projected obliquity measured by the RM effect (see Sect.…”
Section: Hat-p-36 Starspotsmentioning
confidence: 74%
“…Particularly for stars rotating significantly slower than the planet's orbital period, the spot will have moved a little by the time the planet returns in transit. An inclined planet will more easily miss the spot as it rotates out of the transit chord, but an aligned planet is likely to encounter the spot on a few occasions Sanchis-Ojeda and Winn 2011;Nutzman et al 2011;Mancini et al 2014;Močnik et al 2016;Dai et al 2017). The timing of starspot crossings can also be combined with out-of-transit variations to estimate the spin-orbit angle (Sanchis-Ojeda et al 2012).…”
Section: Alternate Means To Measure the Spin-orbit Angle Of Exoplanetsmentioning
confidence: 99%
“…This weakness is especially serious when the technique is applied to ground-based data, for which quasi-continuous monitoring is very difficult to achieve. For example, Mancini et al (2014) did not have the stellar rotation period as an independent check for their model of Qatar-2b. By assuming that two particular spot-crossing anomalies they observed were associated with a single spot, they derived a stellar rotation period of 14.8±0.3 days (as later revised by Mancini et al 2016).…”
Section: Anomaly Identification and Timingmentioning
confidence: 99%